Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 206522 by MrGHK last updated on 17/Apr/24

Answered by Berbere last updated on 17/Apr/24

u′=xln^2 (x)⇒u=(1/2)(x^2 ln^2 (x)−x^2 ln(x)+(x^2 /2))  v=Li_2 (((1+x)/x));v′=−(1/x^2 ).−((ln(−(1/x)))/((1+x)/x))=−((ln(−x))/(x(1+x)))  IBP  =(1/2)[(x^2 ln^2 (x)−(x^2 /2)ln(x)+(x^2 /2))Li_2 (((1+x)/x))]_0 ^1   +(1/2)∫_0 ^1 (x/(1+x))ln(−x)(xln^2 (x)−xln(x)+(x/2))dx  “Li_2 (z)+Li_2 (1−(1/z))=−(((ln(z))^2 )/2) ”  ⇒Li_2 (((1+z)/z))=Li_2 (−z)−(1/2)(ln(−z))^2 ⇒lim_(x→0) xLi_2 (((1+x)/x))=0  A=(1/4)Li_2 (2)+(1/2)∫_0 ^1 ((x^2 ln^2 (x)ln(−x))/(1+x))−(1/2)∫_0 ^1 ((x^2 ln(x)ln(−x))/(1+x))dx  +(1/4)∫_0 ^1 (x^2 /(1+x))ln(−x)dx  ln(−x)=ln(x)+iπ  ∫_0 ^1 ((x^2 ln^n (x)ln(−x))/(1+x))dx  =∫_0 ^1 ((x^2 ln^(n+1) (x))/(1+x))dx+iπ∫_0 ^1 ((x^2 ln^n (x)dx)/(1+x))=  ∫_0 ^1 ((x^2 ln^m (x))/(1+x))=Σ_(n≥0) (−1)^n x^(n+2) ln^m (x)dx=H(m)  =Σ_(n≥0) (−1)^n ∫_0 ^1 x^(n+2) ln^m (x)=Σ_(n≥0) (−1)^n ∫_0 ^∞ (−t)^m e^(−(n+2)t) dt  =(−1)^m Σ_(n≥0) (((−1)^n Γ(m+1))/((n+2)^(m+1) ))=(−1)^m m!(Σ_(n≥0) (((−1)^(n+2) )/((n+2)^(m+1) )))  =(−1)^m m!(Σ_(n≥1) (((−1)^n )/n^(m+1) )+1)  Σ_(n≥1) (((−1)^n )/n^(m+1) )=(1−(1/2^m ))ζ(m+1);∀m≥1  H=(−1)^m m!((1−(1/2^m ))ζ(m+1)+1)  A=((Li_2 (2))/4)+(1/2)∫_0 ^1 ((x^2 ln^3 (x))/(1+x))+((iπ)/2)∫_0 ^1 ((x^2 ln^2 (x))/(1+x))dx−(1/2)∫_0 ^1 ((x^2 ln^2 (x))/(1+x))+(1/2)∫_0 ^1 x^2 ((iπln(x))/(1+x))dx  +(1/4)∫_0 ^1 ((x^2 ln(x))/(1+x))dx+((iπ)/4)∫_0 ^1 (x^2 /(1+x)) dx   =((Li_2 (2))/4)+(1/2)H(3)−((H(2))/2)+(1/4)H(1)+((iπ)/2)(H(2)+H(1))  +i(π/2)∫_0 ^1 (x^2 /(1+x))dx easy To continue

u=xln2(x)u=12(x2ln2(x)x2ln(x)+x22)v=Li2(1+xx);v=1x2.ln(1x)1+xx=ln(x)x(1+x)IBP=12[(x2ln2(x)x22ln(x)+x22)Li2(1+xx)]01+1201x1+xln(x)(xln2(x)xln(x)+x2)dxLi2(z)+Li2(11z)=(ln(z))22Li2(1+zz)=Li2(z)12(ln(z))2limx0xLi2(1+xx)=0A=14Li2(2)+1201x2ln2(x)ln(x)1+x1201x2ln(x)ln(x)1+xdx+1401x21+xln(x)dxln(x)=ln(x)+iπ01x2lnn(x)ln(x)1+xdx=01x2lnn+1(x)1+xdx+iπ01x2lnn(x)dx1+x=01x2lnm(x)1+x=n0(1)nxn+2lnm(x)dx=H(m)=n0(1)n01xn+2lnm(x)=n0(1)n0(t)me(n+2)tdt=(1)mn0(1)nΓ(m+1)(n+2)m+1=(1)mm!(n0(1)n+2(n+2)m+1)=(1)mm!(n1(1)nnm+1+1)n1(1)nnm+1=(112m)ζ(m+1);m1H=(1)mm!((112m)ζ(m+1)+1)A=Li2(2)4+1201x2ln3(x)1+x+iπ201x2ln2(x)1+xdx1201x2ln2(x)1+x+1201x2iπln(x)1+xdx+1401x2ln(x)1+xdx+iπ401x21+xdx=Li2(2)4+12H(3)H(2)2+14H(1)+iπ2(H(2)+H(1))+iπ201x21+xdxeasyTocontinue

Commented by MrGHK last updated on 18/Apr/24

thanks sir Nice solution

thankssirNicesolution

Commented by Berbere last updated on 18/Apr/24

withe Pleasur

withePleasur

Terms of Service

Privacy Policy

Contact: info@tinkutara.com